2016
DOI: 10.1902/jop.2015.150175
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐Expression Profiles in Generalized Aggressive Periodontitis: A Gene Network‐Based Microarray Analysis

Abstract: Functions of the identified genes that were involved in gene networks were cellular development, cell growth and proliferation, cellular movement, cell-cell signaling and interaction, humoral immune response, protein synthesis, cell death and survival, cell population and organization, organismal injury and abnormalities, molecular transport, and small-molecule biochemistry. The data suggest new networks that have important functions as humoral immune response and organismal injury/abnormalities. Future analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 29 publications
5
33
0
Order By: Relevance
“…CNC network analysis of RANKL‐associated lncRNAs showed a strong positive correlation of RANKL with lncRNA BMS1P20 (NR_027293). Previous studies have reported lncRNA BMS1P20 as up‐regulated in aggressive and chronic periodontitis, and similarly, we noted significantly higher BMS1P20 expression levels in three comparisons (I vs H, P vs H, and I vs P). BMS1P20 lies in the immunoglobulin lambda (IgL) gene cluster on chromosome 22q11.21, which is related to B cells and plasma cell function .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…CNC network analysis of RANKL‐associated lncRNAs showed a strong positive correlation of RANKL with lncRNA BMS1P20 (NR_027293). Previous studies have reported lncRNA BMS1P20 as up‐regulated in aggressive and chronic periodontitis, and similarly, we noted significantly higher BMS1P20 expression levels in three comparisons (I vs H, P vs H, and I vs P). BMS1P20 lies in the immunoglobulin lambda (IgL) gene cluster on chromosome 22q11.21, which is related to B cells and plasma cell function .…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, the expression of MZB1 was significantly higher in peri‐implantitis than in periodontitis and was verified by qRT‐PCR MZB1 is a B‐cell‐specific and endoplasmic reticulum localized protein which takes part in the antibody secretion and the integrin‐mediated cell adhesion . A previous study of generalized aggressive periodontitis found MZB1 as most up‐regulated . While the specific role of this gene in peri‐implantitis remains unknown, together, these findings may suggest heightened plasma cell activity in peri‐implantitis lesions as has been previously noted in immunohistological analysis .…”
Section: Discussionsupporting
confidence: 73%
“…also identified a significant decrease in expression of DSC1 in these patients. Interestingly, a lower expression of genes related to epithelial development and adhesion reported in these previous studies was correlated with phenotype and disease activity . These findings in healthy gingival tissues of patients with GAgP may represent a disruption of tissue homeostasis and could have an impact on clinical development of the disease.…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, GAgP was characterized by the underexpression of genes involved in proliferation, differentiation, and cornification of keratinocytes, compared with both CP and H groups. These biologic processes and pathways have already been found to be downregulated in inflamed gingival tissues of AgP compared with patients with CP and healthy patients by previous studies . Kebschull et al .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation